Environmentally sound destruction of hexabromocyclododecanes in polystyrene insulation foam at commercial-scale industrial waste incineration plants. Issue 4 (August 2017) - Kajiwara, Natsuko; Noma, Yukio; Sakai, Shinichi
Highlights: HBCD-containing XPS foam was co-incinerated in nine commercial-scale incinerators. Environmentally sound destruction of HBCDs (DE > 99.999%) was achieved. PBDD/F formation during HBCD co-incineration was virtually negligible. HBCDs were discharged mainly into the bottom ash owing to their fire retardancy. HBCD concentration in bottom ash was negatively correlated with DE. Abstract: To evaluate factors influencing the destruction efficiency (DE) of hexabromocyclododecanes (HBCDs) in end-of-life extruded polystyrene (XPS) insulation foams, we conducted co-incineration tests at nine commercial-scale industrial waste incineration plants in Japan with various furnace types and with capacities ranging from 70 to 350 t/day. Source materials consisting of 0.34–3.3 wt% of XPS insulation foam (HBCD content, 3.4–5.0 wt%) mixed with baseline industrial wastes were co-incinerated at temperatures of 880–1, 210 °C, depending on the plant. HBCD DEs exceeded 99.999% at all the plants (at five plants, the DEs exceeded 99.9999%), with negligible discharge of brominated dioxins and furans. The type of furnace, the incineration temperature, the air pollution control system, and the XPS/waste mixing ratio had no obvious effect on DE. Except at two plants, more than approximately 80% of the total HBCD output was found in the bottom ash, implying that undecomposed HBCDs are discharged unburned into the bottom ash owing to their fire retardancy. HBCD concentrations in bottom ash (<0.01–40 ng/g-dry) and DE (99.9992–99.999998%) were negatively correlated, suggesting that at XPS/waste mixing ratios of up to approximately 3 wt%, HBCD residue concentrations in bottom ash may be a useful indicator that DE exceeds 99.999%.